Feeding Abundantia: exploring critical issues in food security - Dentzer, Susan; Rose, Barbara (International Food Policy Research Institute, 1996)
A Guide to the 2020 Vision Video, Feeding Abundantia, a Roundtable Debate about Food Security in a Hypothetical Developing Country Despite the diversity of perspectives, it is increasingly clear that there are potential solutions to both present and future food insecurity. Capturing them is the goal of this panel discussion. The panel features a number of real-life government officials, representatives of nongovernmental organizations, academics, and other experts who bring their perspectives on food security to the case of a hypothetical developing country -- Abundantia.